Economic Development Challenges for Immigrant Retail Corridors: Observations From Chicago's Devon Avenue. (November 2017) - Gandhi, Akshali; Minner, Jennifer
Immigrant entrepreneurship is important to local and regional economies, cultural identity, placemaking, and tourism. Meanwhile, regional conditions, such as the development of suburban immigrant gateway communities and increases in the cost of business ownership, complicate local economic development efforts in urban ethnic districts. This research is presented as a mixed–methods case study of Devon Avenue in Chicago, IL, home to a significant concentration of South Asian–owned immigrant businesses. Challenges and pressures facing businesses are examined through merchant surveys and interviews. Observations reinforce the notion that cultural competency and strong grassroots leadership is vital for economic development planning so that "capitalizing" on an ethnic heritage does not become a tool for commodification or commercial gentrification. Agencies must also be mindful of the impacts associated with suburbanization of immigrant communities and take a long-term, regional approach to planning in ethnic commercial corridors.